The Influence of E-WOM through Traveling Vlogs on TikTok on Tourists’ Visit Decisions to a Destination - Wulandari, Fahra Putri; Rosita; Marhanah, Sri (Research Horizon, 2025)
With the rapid development of the internet and social media, Electronic Word of Mouth (E-WOM) has become a powerful medium for sharing information and shaping public perception. This study explores how E-WOM influences individuals’ decisions to visit tourism destinations, focusing particularly on travel related content shared through TikTok. This study applies a quantitative survey design with purposive sampling of 250 valid respondents who are active TikTok users and prospective tourists. Data were analyzed using descriptive statistics, validity and reliability tests, and regression use SPSS.  Although certain data patterns showed irregularities, the overall analysis confirms a clear and consistent connection between the two variables. This study confirms that E-WOM disseminated through travel vlog content on TikTok has a positive and significant influence on tourists’ decisions to visit a destination. The findings emphasize the strategic importance of managing digital narratives on social media platforms, encouraging tourism stakeholders to pay closer attention to how content is created and perceived. This research offers practical insights for enhancing digital marketing strategies and opens further opportunities to investigate other influencing factors in tourism decision making within the digital era.